2023
DOI: 10.1186/s12913-023-09744-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotional support on healthcare workers and students coping with COVID-19, and other SARS-CoV pandemics – a mixed-methods systematic review

Abstract: Background Pandemics such as COVID-19 pose threats to the physical safety of healthcare workers and students. They can have traumatic experiences affecting their personal and professional life. Increasing rates of burnout, substance abuse, depression, and suicide among healthcare workers have already been identified, thus making mental health and psychological wellbeing of the healthcare workers a major issue. The aim of this systematic review is to synthesize the characteristics of emotional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These include reduced quality of care, absenteeism, turnover, and reduced commitment (27). Providing emotional support interventions for intern nursing students is required (66). To reduce anxiety and stress, the faculty should create a structured learning environment, follow the course schedule, communicate changes or updates promptly, modify assignments to fit the learning environment, take self-care, extend grace, and make use of campus, local, and national resources (67).…”
Section: Working With An Experienced Teammentioning
confidence: 99%
“…These include reduced quality of care, absenteeism, turnover, and reduced commitment (27). Providing emotional support interventions for intern nursing students is required (66). To reduce anxiety and stress, the faculty should create a structured learning environment, follow the course schedule, communicate changes or updates promptly, modify assignments to fit the learning environment, take self-care, extend grace, and make use of campus, local, and national resources (67).…”
Section: Working With An Experienced Teammentioning
confidence: 99%
“…Reliable social support in the workplace and in their personal lives (Effendy et al, 2023 ) appears instrumental in fostering this positive transformation. Several online emotional support programmes from healthcare workers and trainees have been evaluated during the pandemic, showing evidence of effectiveness in reducing distress and promoting positive emotions and support seeking (Harkanen et al, 2023 ). However, another study found that frontline healthcare workers preferred support from colleagues, family, or psychologists in person to virtual services such as hotlines.…”
Section: Emotional Support and Posttraumatic Growthmentioning
confidence: 99%
“…Before the pandemic there had been studies that evaluated mental health interventions for HCWs at the individual (Tamminga et al 2023) or organizational level (Gray et al 2019), without providing good evidence for specific interventions. The start of a pandemic was not an environment for the cluster randomized trials that might have resulted in clear evidence of benefit of workplace mental health programs, but a number of short-term interventions were assessed in controlled trials (Amsalem et Härkänen et al 2023) but again without specific recommendations as to the type of intervention, while recognizing the need both for better support with both employee and employer engagement and for more research.…”
Section: Introductionmentioning
confidence: 99%
“…The start of a pandemic was not an environment for the cluster randomized trials that might have resulted in clear evidence of benefit of workplace mental health programs, but a number of short-term interventions were assessed in controlled trials (Amsalem et al 2022; Coifman et al 2021; Fiol-DeRoque et al 2021). There have been thoughtful reviews of support programs put in place for HCWs during the pandemic (Buselli et al 2021; Villarreal-Zegarra et al 2022; David et al 2022; Härkänen et al 2023) but again without specific recommendations as to the type of intervention, while recognizing the need both for better support with both employee and employer engagement and for more research.…”
Section: Introductionmentioning
confidence: 99%